Leveraging Indigenous Knowledge through Technology to Enhance Creativity and Critical Thinking in Students - Sikya Nodin Mika (PT. Islamic Research Publisher, 2025)
This study explores the integration of indigenous knowledge with technology to enhance students’ creativity and critical thinking. The main objective is to investigate how digital tools can facilitate the application of local wisdom in educational contexts and how such integration affects cognitive and higher-order thinking skills. Employing a mixed-methods approach, the research combined a quasi-experimental design with pre- and post-tests to quantitatively measure creativity and critical thinking improvements, alongside qualitative interviews to capture students’ experiences, perceptions, and engagement with technology-mediated indigenous knowledge. The study was conducted among students in [specify region or school level if needed], where local cultural practices are rich and varied. Findings reveal that students participating in technology-enhanced indigenous knowledge activities showed a statistically significant increase in creativity and critical thinking compared to control groups. Qualitative analysis further indicates that students developed stronger problem-solving abilities, higher cultural awareness, and greater motivation to apply local knowledge in innovative ways. The integration of technology not only supported interactive and collaborative learning but also provided a meaningful context for connecting academic concepts with students’ cultural backgrounds. This research contributes to the field of educational innovation by offering an empirically validated framework for leveraging indigenous knowledge through technology, emphasizing the importance of contextualization, participation, and transformation in learning. The study also provides practical implications for curriculum developers, educators, and policymakers seeking to design pedagogical strategies that foster higher-order thinking skills while preserving and promoting local wisdom. Ultimately, this approach encourages a balanced development of cognitive, creative, and cultural competencies in students, highlighting the potential of culturally responsive and technology-mediated education in contemporary learning environments.